Personal Agency in Borderline Personality Disorder: The Impact of Adult Attachment Style - Hashworth, Talia; Reis, Samantha; Grenyer, Brin F. S. (Frontiers in Psychology, 2021)
Background: Personal agency- the degree to which one believes they have control over their life- is thought to influence how people understand their interpersonal relationships. Links between adult attachment and personal agency are theoretically relevant to the experience of borderline personality disorder (BPD) but this has yet to be empirically examined. The present research examines the impact of personal agency and adult attachment styles for individuals meeting criteria for BPD. Methods: Participants consented to an online community study examining measures of locus of control (as an index of personal agency), BPD, and adult attachment. Participants meeting criteria for BPD (N=96; mean age=30.63; 70.5% female) were compared to age-matched healthy controls (N=96; mean age= M=31.99; 89.0 % female). Results: Individuals who met criteria for BPD displayed lower personal agency and higher fearful and preoccupied attachment styles in their close relationships, compared to Controls. Controls reported greater personal agency and were more securely attached in their relationships. Using multiple mediation modelling, the indirect effect of personal agency on BPD was significant for preoccupied, fearful, and secure attachment, but was non-significant for dismissive attachment. Lower personal agency was associated with insecure adult attachment styles. Conclusions: Findings highlight the previously unexplored relationship between BPD and personal agency and indicate that adult attachment style plays a significant role. Low personal agency may increase challenges for individuals with symptoms of BPD by exacerbating relationship difficulties. People in treatment for BPD may benefit from focusing on both relationship insecurity and its impact on their perceived personal control.